Vocational Students’ Conception about Mathematics as Sensible Based on Personality Types - Amirul Khumaini Sholli; Agung Lukito; Rini Setianingsih (International Journal of Trends in Mathematics Education Research, 2020)
The aim of this study is describing students’ conception about mathematics as sensible based on personality types. This study is a descriptive study with qualitative approach. Subjects of this study are four female vocational students with guardian type, artisan type, rational type, and idealis type with equivalent mathematics ability and feminine gender orientation. The selection of subjects was held through personality test, mathematics ability test, and gender orientation questionnaire. The data were collected by giving problem solving task and task-based interview.The result showed that there are some differences on students’ conception about mathematics as sensible based on personality type. Students with guardian type, Artisan type, and rational type planed a problem solving strategy based on their previous experience, while student with Idealis type planed a problem solving strategy based on the mathematics concept related to the problem. Students with Guardian type and Rational type planed alternative strategy in solving problem to get better solution. Another difference is in explaining the reason of using strategy. Student with Rational type didn’t explain the reason of using the problem solving strategy